The REKAYASA PERANGKAT LUNAK SISTEM INFORMASI AKADEMIK DI SMK TERPADU BANI RUSYDI CIMARGA - Waliadi Gunawan; Achmad Machromi Nur (Journal of Innovation And Future Technology (IFTECH), 2019)
The development of current computer technology with the speed of the process has enabled developers of computer-based information systems, which makes it easy for users from various fields. The preparation of this thesis discusses the creation of a web-based academic information system in the Integrated Vocational School of Bani Rusydi Cimarga. After conducting research, the authors found the problems that exist in the work unit, among others, from the data processing in the academic section has not used an integrated database system. In the processing of the schedule does not use a system that is integrated with the subject database and the teacher database. Not yet integrated between the student database in the financial section and the student database in the student / BK section. Not yet integrated between the teacher's value database with the value database in the curriculum, these problems make the performance process less effective and require a relatively longer time. From the results of the analysis that has been done, the idea is obtained that a computerized system is needed for the purposes of data processing, schedule processing, and value processing. In order for the academic system currently running at Bani Rusydi Integrated Vocational School to process data, process UTS / UAS cards and process student grades, an integrated academic information system application needs to be made.